Feeding the cosmos: tackling personalized space nutrition and the leaky gut challenge - B. Barbero Barcenilla; R. Rivero; A. Lynch; W. Cromer; J. Gong; B. Harandi; M. Stegmann; H. Le; D. Lundine; M. Chung; J. Puig; K. Mikhailova; et al. (npj Microgravity)
Abstract Long-duration space missions pose serious challenges to astronaut nutrition and health due to the altered environment of Low Earth Orbit (LEO). This study examines the nutritional composition of crops grown in space, identifying deficiencies in key nutrients such as calcium and magnesium, along with variable antioxidant profiles. These imbalances may impact astronaut physiology, particularly bone health and immune function, and are potentially linked to altered gene expression pathways in microgravity. Emerging evidence also suggests increased intestinal permeability, referred as leaky gut syndrome, which further disrupts nutrient absorption and immune regulation. To mitigate these issues, we evaluate targeted strategies including bioengineering of nutrient-dense crops, incorporation of antioxidant-rich species, and personalized nutrition guided by pharmacogenomics. Approaches such as biofortification and tailored supplementation are proposed to address these challenges. This work contributes to the development of resilient space agriculture systems that support astronaut health during deep space missions and future planetary habitation.